2018
DOI: 10.1002/14651858.cd012054.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase attendance for diabetic retinopathy screening

Abstract: This is the published version of the paper.This version of the publication may differ from the final published version. Permanent repository link: T A B L E O F C O N T E N T S A B S T R A C TThis is the protocol for a review and there is no abstract. The objectives are as follows:The primary objective of the review is to assess the effectiveness of intervention components that seek to increase attendance for diabetic retinopathy screening in people with type 1 and type 2 diabetes. Secondary objectives:• To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 146 publications
3
63
0
1
Order By: Relevance
“…A recent Cochrane review of 66 randomized, controlled trials in type 1 and type 2 diabetes demonstrated only a modest 12% increase in DRS attendance with QI strategies, consistent with our data and indicating how difficult it is to improve this metric ( 5 ). Patients at highest risk of diabetic retinopathy, including those with poor glycemic control, who have lower socioeconomic status, or who have diabetes complications such as microalbuminuria, have been demonstrated to be least likely to undergo DRS ( 3 , 6 ).…”
Section: What Are Your Next Steps?supporting
confidence: 89%
“…A recent Cochrane review of 66 randomized, controlled trials in type 1 and type 2 diabetes demonstrated only a modest 12% increase in DRS attendance with QI strategies, consistent with our data and indicating how difficult it is to improve this metric ( 5 ). Patients at highest risk of diabetic retinopathy, including those with poor glycemic control, who have lower socioeconomic status, or who have diabetes complications such as microalbuminuria, have been demonstrated to be least likely to undergo DRS ( 3 , 6 ).…”
Section: What Are Your Next Steps?supporting
confidence: 89%
“…One review described interventions to promote DRS uptake [28]. In addition, there was another Cochrane review on quality improvement interventions to increase DRS attendance [29]. Another recently published review has also considered the barriers to access DRS without specifying the setting [30].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we used an in-depth interview method to explore the influencing factors on the compliance of timely visits among patients with proliferative diabetic retinopathy, and found that more than 90% of the patients were lacking knowledge about DR [12]. A recent Cochrane review showed that interventions to increase awareness about DR are vital in improving attendance for DR screening, and thus a potentially important solution for reducing blindness caused by DR [13]. Therefore, patient awareness and knowledge about DR will be the key to successful disease management and prevention.…”
Section: Introductionmentioning
confidence: 99%